Nicotinic acid improves mitochondrial function and associated transcriptional pathways in older inactive males - Deane Colleen S.; Willis Craig R. G.; Gallagher Iain J.; Brook Matthew S.; Gharahdaghi Nima; Wylie Lee J.; Wilkinson Daniel J.; Smith Kenneth; Atherton Philip J.; Etheridge Timothy (Translational Exercise Biomedicine)
To examine the effect of the NAD+ precursor, nicotinic acid (NA), for improving skeletal muscle status in sedentary older people.